Les épreuves professionnelles dans la fonction de tuteur : une étude comparative sur les formateurs de terrain de l’Education nationale française - Eric Maleyrot (Recherches en Éducation)
This comparative study focuses on the professional ordeals into the tutor’s function of two categories of mentor teachers working in Education in France before the implementation of the 2010 reforms of initial teacher training. These are master trainers who work in the primary school and pedagogic tutor counselors employed in the second degree. These professionals have a dual role of teacher with pupils and trainer in charge to help future teachers for entry into the profession. Considering the training devices as an expression of an institutional project on professionals and these professionals’ commitment as an indicator of their professional personal project, we examine the relation between these two projects by focusing on ordeals they face in their work as tutors. In the first time, this article compares the official texts which rule the trainers’ employment and their training activities. Secondly, from 18 semi-structured interviews, we find out professional ordeals experienced by each category of trainers. Finally, we highlight the "standardized system of professional ordeals" of these tutors and then by comparison, we determine the nature of their common ordeals and those specific to each class of tutors.